2016
DOI: 10.1016/j.actbio.2016.03.039
|View full text |Cite
|
Sign up to set email alerts
|

In vivo monitoring the biodegradation of magnesium alloys with an electrochemical H2 sensor

Abstract: Biomedical devices such as plates and screws used for broken bone repair are being developed out of biodegradable magnesium alloys that gradually dissolve when no longer needed. This avoids subsequent removal by surgery, which may be necessary if complications arise. A rapid, non-invasive means for monitoring the biodegradation process in vivo is needed for animal testing and point of care (POC) evaluation of patients. Here we report a novel, simple, fast, and noninvasive method to monitor the biodegradation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 55 publications
(87 reference statements)
4
49
0
Order By: Relevance
“…The sensor-based monitoring system may have some overlaps with that of electrochemicalbased. A set-up developed by Zhao et al [71] can be put in this category. In this non-invasive set-up Another electrochemical-based system was developed to monitor the real-time corrosion of Mg, namely the corrosion characterization system [67].…”
Section: Sensor-based Monitoring Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensor-based monitoring system may have some overlaps with that of electrochemicalbased. A set-up developed by Zhao et al [71] can be put in this category. In this non-invasive set-up Another electrochemical-based system was developed to monitor the real-time corrosion of Mg, namely the corrosion characterization system [67].…”
Section: Sensor-based Monitoring Systemmentioning
confidence: 99%
“…The sensor-based monitoring system may have some overlaps with that of electrochemical-based. A set-up developed by Zhao et al [71] can be put in this category. In this non-invasive set-up (Figure 7a), the real-time concentration of hydrogen gas is measured by a micro-sensor, and they used it to study the corrosion behavior of an Mg alloy in-vivo (Figure 7b).…”
Section: Sensor-based Monitoring Systemmentioning
confidence: 99%
“…These parameters could be used to model the degradation process and the formation of the interface in vivo, providing indirect information about the degradation layer. The release of H 2 can be monitored optically or electrochemically from outside of the body 28,29 if the implant is placed subcutaneously. These measurements allow noninvasive quantification of H 2 but not permanent monitoring of its evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has used an electrochemical (amperometric) H2 sensor to monitor the corrosion process of implanted rare earth-containing Mg alloys, other Mg alloys and high purity Mg single crystal disks in mice [22,30,31]. One study showed that there is little difference between the H2 concentration inside a gas cavity associated with a subcutaneous implant and a transdermal measurement made on the skin above the implant [30,31]. This observation confirmed the extraordinarily fast transport of H2 through biological tissues such as skin, which also means that H2 levels in vivo can potentially be tracked noninvasively by a H2 sensor measuring transdermally by simply pressing it against the skin.…”
Section: Introductionmentioning
confidence: 99%